Livsmod - Pahuus, Mogens (Nordisk tidsskrift for helseforskning, 2019)
Courage to beIn the first part of the essay the question is: What is and what characterizes courage to be? - I here distinguish between courage to be in children, where it is attached to children´s play, and the courage to be in adults, where ist combined with self-conquest and with integration of the ability to act purposely. I stress five dimensions in courage to be: power, possibility, vitality, courage and meaning. It is made clear, that even if courage to be in adults are not attached to bodily unfolding, yet it is stored in the body and therefore can be called forth in a bodily way. In the second part of the essay I discuss the relation between courage to be on one side and fear of life, selfishness and joy of life on the other side. It is demonstrated, that what nourishes and maintains courage to be is joy of life and self-devotion. The thesis of the essay is accordingly that courage to be is created and maintained partly by vitality in its different forms, partly by its attachment to joy of life.